MODEL PENYUSUNAN PELAPORAN KEUANGAN BERBASIS GREEN ACCOUNTING : ANALISIS STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR UNTUK MENDUKUNG TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS). - Saepul Anwar; Susy Hambani; Fitra Weli; Annisa Lutfiah Zahra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
Company financial reporting currently requires financial allocation towards aspects of environmental empowerment in the form of corporate responsibility which is recognized as part of a company's investment as part of the green accounting implementation component, however the facts on the ground show that not all companies understand the concept of green accounting and how to implement it. in its financial reporting, this research aims to be able to analyze how the concept of green accounting is applied empirically in a company in the form of accountability in financial reports as part of efforts to support sustainable development (SDGS) which in this case is applied to the company PT companies operating in the sector manufacturing. The methodology used in this research uses in-depth observation techniques through direct problem analysis techniques through observation and documentary techniques. The results of this research show that company management has implemented several green accounting concepts in the management or governance of its financial reporting, such as in the profit and loss report component, although it has not been carried out optimally, this is because the balance sheet component has not yet reported responsibility for the allocation of costs in green accounting that has been carried out. The novel value that this research tries to offer is related to the model for preparing financial reporting in companies using a green accounting element base